1989
DOI: 10.1128/aac.33.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhibitory activities of various antiretroviral agents against particle-derived and recombinant human immunodeficiency virus type 1 reverse transcriptases

Abstract: Several known antiretroviral agents were tested for their ability to inhibit the activities of human immunodeficiency virus type 1 reverse transcriptase purified from virions or from a recombinant Escherichia coli strain. The recombinant reverse transcriptase, a polypeptide of 66 kilodaltons, showed inhibition profiles indistinguishable from those of the virion-derived enzyme with all tested compounds, except for suramin and two dextran sulfates. These were more inhibitory to the recombinant enzyme, presumably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…When HIV reverse transcriptase-containing supernatants (-100,000 cpm/ml) were incubated with therapeutic anti-HIV concentrations of the dextran sulfates (30 min at 37°C), no reverse transcriptase activity was detected. Since the dextran sulfates interfered with the reverse transcriptase determination, this parameter of HIV expression was not utilized for the antiviral evaluations (26).…”
Section: Methodsmentioning
confidence: 99%
“…When HIV reverse transcriptase-containing supernatants (-100,000 cpm/ml) were incubated with therapeutic anti-HIV concentrations of the dextran sulfates (30 min at 37°C), no reverse transcriptase activity was detected. Since the dextran sulfates interfered with the reverse transcriptase determination, this parameter of HIV expression was not utilized for the antiviral evaluations (26).…”
Section: Methodsmentioning
confidence: 99%
“…We found that the inhibition pattern of MuLV RT was significantly different from that of HIV-1 RT. The RNase H activity, for example, was about twofold less sensitive to illimaquinone; the calculated IC50 was approximately 29 jiM. On the other hand, the RDDP and DDDP activities of MuLV RT were more susceptible to the inhibitory compound (IC50s of about 19 and 15 jig/ml, respectively) than the corresponding functions of HIV-1 RT (more than 50 ,ug/ml for both activities; Table 1).…”
mentioning
confidence: 99%
“…However, it is highly likely that residual drug may inactivate the virus directly, resulting in an overestimation of the potency of the fulleroid in chronically infected H9 cells. The compound was also evaluated for its inhibitory effect on recombinant p66/51 HIV-1 RT by using poly(rA)n oligo(T) 12 18 as the template-primer (17). Compound 1 was active against this enzyme, with a median inhibitory concentration (IC50) of 4.6 ,uM.…”
mentioning
confidence: 99%